Cognitive Behavioral Interventions for Mental Health Practitioners / Mental Health in Practice - Grant Alec (Learning Matters, 2010)
Mental Health in Practice is an exciting new series of books for mental health professionals and practitioners. It combines academic theory with the practical realities of working in the field of mental health and is packed full of activities and features to reinforce learning. Acknowledgements, Introduction, A Brief History of Cognitive Behavioral Therapy, Unmet Need: Policy Related Recommendations, Client Preparation and Assessment, Helping Anxious People, Helping People Who are Low in Mood, Helping People Who Hear Voices and Have False Beliefs, Helping People with Borderline Personality Disorder, Conclusion, Glossary, References, Index.